2017
DOI: 10.9782/2159-4341-20.2.67
|View full text |Cite
|
Sign up to set email alerts
|

Examining Self-Monitoring Interventions for Academic Support of Students with Emotional and Behavioral Disorders

Abstract: Researchers have found that English teachers in the United States of America (USA) perceive providing writing instruction to students with emotional behavioral disorders (EBD) as a difficult task. This could be associated with the fact that students with EBD often work below skill level in the content area of writing compared to same age peers. Researchers continue to investigate interventions to increase academic outcomes for students with EBD. Utilizing a single case design, three middle school students with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Second, the portability of mobile technology (e.g., iPad, iPod, or a handheld computer in early 2000s) made it possible for students to use the technology frequently. For example, students in Bruhn et al (2017)'s study used the technology at 10‐minute intervals and students in Hunter et al (2017)'s study used the technology at 5‐minute intervals during regular lessons. While the use of technology during instruction could distract those who are not good at multi‐tasking (Mayer & Moreno, 2010), the studies showed that the technology kept the students engaged.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the portability of mobile technology (e.g., iPad, iPod, or a handheld computer in early 2000s) made it possible for students to use the technology frequently. For example, students in Bruhn et al (2017)'s study used the technology at 10‐minute intervals and students in Hunter et al (2017)'s study used the technology at 5‐minute intervals during regular lessons. While the use of technology during instruction could distract those who are not good at multi‐tasking (Mayer & Moreno, 2010), the studies showed that the technology kept the students engaged.…”
Section: Discussionmentioning
confidence: 99%
“…,Blood et al (2011), Cihak et al (2010), Hunter et al (2017,Romans et al (2020), Rosenbloom et al (2019,Szwed and Bouck (2013). The heterogeneity value, I 2 , was 0%, meaning there was no significant difference in the effects oftechnology-based self-monitoring interventions across the selected studies, indicating the overall effectiveness of the technology-based self-monitoring interventions.…”
mentioning
confidence: 97%
“…First, TBSM tools or applications are user-friendly. Researchers have suggested that TBSM tools are “portable,” “easy to use,” “socially acceptable,” and “students are motivated to use them” (Bauer & Ulrich, 2002; Hunter et al, 2017, p. 68). Second, TBSM approaches are efficient, requiring less effort from adults than other approaches to support student behavior.…”
Section: Evidence Supporting Tbsm In Schoolsmentioning
confidence: 99%
“…For educators, the more time students engage in off-task behavior, the more time educators must spend addressing off-task behavior rather than delivering academic instruction (Gage et al, 2018).Off-task behavior may have an even more detrimental impact on students with or at risk for emotional and behavioral disorders (EBD). Compared with typically developing students, students with EBD are more likely to have lower levels of on-task behavior performance and task completion (Hunter et al, 2017). Therefore, it is critical to identify effective strategies to support all students, including students with or at risk for EBD, to engage in learning and increase on-task behavior.…”
mentioning
confidence: 99%